(untitled) (Педагогіка вищої та середньої школи, 2006)
The article dwells upon the problem of teaching Anglistics as a set o f subjects interconnected and interdependent. A plan for studying this set o f subjects at the English Language Departments of Universities is made for the whole 5-year period of studies; it takes into account possible variants of interdisciplinary ties and connections. Primary attention is paid to English-language literature as a source of variegated means of improving students’ skills of philological analysis as well as a device for studying English and American mentality.